Høyere utdanning i tre dimensjoner En ny teoretisk forståelsesramme - Haukland, Linda Helén (Orkana Forlag AS, 2021)
«Higher Education in three Dimensions. A New Theoretical Frame of Understanding» consists of three parts. Part one is an institutional analysis of the change dynamics in the Norwegian higher education field between 1965 and 2011, which led to the foundation of the University of Nordland, now Nord University. The analysis is based on the foundation of Nordland Regional College and follows the development of the national university and college sectors along with the regional colleges in Bodø up until the foundation of the university. Part II presents a new theoretical frame of understanding for analysing the development driven by these tensions and other factors. It questions the two-dimensional understanding of terms as autonomy and academic drift, and suggests society at large as a stronger third dimension in the analysis of higher education. Part III concludes on that a three-dimensional framework of understanding highlights new key themes, issues and dilemmas in the field of higher education. It is therefore both fruitful and needed as a greater depth of understanding is achieved, comparative analysis is made possible and dilemmas at stake are revealed.